Design of a spherical array self-mixing oscillator antenna - Krairiksh, Monai; Buasomboon, Wanlika; Ngamjanyaporn, Phaisan; Phongcharoenpanich, Chuwong (My University, 2001)
Principle of a spherical array self-mixing oscillator antenna is discussed in this paper. Applying the injection locking technique to the spherical array which elements are made of simple waveguide radiators, the beam steering with considerably constant pattern in different directions can be achieved without using the sophisticated phase shifters. This antenna is designed and tested at the frequency of 10 GHz.